(untitled) (Research, Society and Development, 2021)
The aim of this study was to assess the functional capacity of institutionalized older people and to verify which sociodemographic, health factors and oral health were related to the worse ability to perform daily activities. It was a cross-sectional study conducted with 512 institutionalized elderly people. Sociodemographic profile; general health and oral health conditions were evaluated. Functional capacity was assessed by Barthel Index. A high prevalence of functional dependent elderly was found (47.1%). A lower functional capacity was associated with female (p=0.006); higher education (p=0.009); older elderly (p<0.045); decision to institutionalize by others (p=0.011); affected cognitive state (p<0.001); reduced mobility (p<0.001), less autonomy for self-care in oral health and worse oral health. Institutionalized elderly has low functional capacity that is related to several aspects of their lives.